Use of soil amendments: Important measure to increase yield in sugar beet - Marius Bǎrdaş; Alina Şimon; Florin Russu; Felicia Cheţan; Ovidiu Adrian Ceclan (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The research where executed in 2021, at the Turda Agricultural Development Research Station, using the Vangelis sugar beet cultivar and followed the influence of Terracalco 95 soil amendments on physiological parameters and production at different stages of crop development. The granular soil amendment was applied in two doses of 500 and 1000 kg/ha-1 , during the vegetation period (beginning of root formation, 75 days after emergence, 105 days after emergence and 135 days after emergence), quantifying certain physiological parameters. Physiological parameters were monitored with the CIRAS-3 foliar gas analyzer, simultaneously determining: reference carbon dioxide (CO2r- μmolms -1 ), assimilation (A- μmol m-2 s -1 ), transpiration rate (E- mmolm-2 s -1 ), leaf water deficit (VPD- kPa) and leaf temperature (Tfr. oC). By applying the granulated soil amendment, the absorption of nutrients is maximized, in most cases stimulating the analyzed physiological parameters, obtaining in the variant that applied 1000 kg/ha-1an increase in production of over 950 kg/ha-1 .
Keywords: Q01; Q15; Q16; 330; soil amendment; assimilation; sugar beet; yield